Analysis of Interest In Learning Islamic Religious Education at State Senior High School 2 Sorong City - Zuliyantika Rizmandani (Fakultas Tarbiyah dan Ilmu Keguruan, 2025)
This study aims to analyze the extent of interest in studying Islamic Religious Education at SMA Negeri 2 Sorong City. By using field research and using a descriptive qualitative research approach. The data collection techniques used are interviews, documentation, and observation. Based on the results obtained from interviews and observations made on students and teachers at SMAN 2 Sorong City, it is clear that there are many factors that influence students' interest in learning, namely internal and external factors. Internal factors are factors that originate from oneself, such as students' high curiosity, high learning motivation, and recognition of students' understanding of learning. Meanwhile, external factors are factors that come from outside the student, such as the teacher's approach, the learning methods used by the teacher, the attention of parents, socio-economic aspects, parental education level, the condition of parents, the atmosphere at home, the relationship between parents and children, and friendly environment.